Review of hydrogen isotope effects on H-mode confinement in JT-60U. (17th June 2021) - Urano, H; Narita, E
Abstract: Hydrogen isotope effects on H-mode confinement in JT-60U are reviewed. The thermal energy confinement time becomes longer in deuterium by a factor of ∼1.4 than in hydrogen at a given absorbed power. When the absorbed power is fixed, the values of electron and ion temperature become evidently higher in deuterium than in hydrogen throughout the entire range of minor radius whereas the electron density profiles are nearly the same. Hence, the effective heat diffusivity becomes relatively lower in deuterium than in hydrogen. When the thermal stored energy is fixed, identical profiles for the electron density, electron temperature, and ion temperature are obtained for hydrogen and deuterium plasmas, whereas the required power clearly increases for hydrogen, which results in reduction of heat diffusivity for deuterium. The inverse of the ion-temperature-gradient (ITG) scale length required for a given ion heat diffusivity increased by a factor of approximately 1.2 for deuterium compared with that for hydrogen. Similar density profiles are formed for the hydrogen and deuterium plasmas despite the higher turbulent particle flux for the hydrogen case, suggesting that turbulent particle transport is more suppressed in the deuterium plasmas. The gyrokinetic calculation indicates that the stabilization effect of e-i collisionality on the TEM is more significant for deuterium plasmas and causes the difference in the quasilinear diffusivity between the two cases. The edge-core interplay leading to the overall H-mode confinement is also addressed where the effect of the hydrogen isotopic composition was involved. The correlation between edge pedestal pressure and global poloidal beta holds true consistently regardless of the difference in the isotopic composition. A higher value of global poloidal beta was obtained for deuterium because of its smaller ITG scale length and because of the additional stored energy in the thermal and fast ion components, the latter due to an increase of slowing down time with an increase of isotopic mass.